Revelation of Potent Epitopes Present in Unannotated ORF Antigens of SARS-CoV-2 for Epitope-Based Polyvalent Vaccine Design Using Immunoinformatics Approach - Uttamrao, Patil Pranita; Sathyaseelan, Chakkarai; Patro, L. Ponoop Prasad; Rathinavelan, Thenmalarchelvi (Frontiers in Immunology, 2021)
SARS-CoV-2 kills thousands of people worldwide every day, thus, necessitating rapid development of countermeasures. Immunoinformatics analyses carried out here in search of immunodominant regions in recently identified SARS-CoV-2 unannotated ORFs (uORFs) has identified 8 linear B-cell, 1 conformational B-cell, 10 CD4+ T-cell and 12 CD8+ T-cell promising epitopes. Among them, ORF9b B-cell and T-cell epitopes are the most promising followed by M.ext and ORF3c epitopes. ORF9b40-48 (CD8+T-cell epitope) is found to be highly immunogenic and antigenic with the highest allele coverage. Further, it has overlap with 4 potent CD4+ T-cell epitopes. Structure based B-cell epitope prediction has identified ORF9b61-68 to be immunodominant, which partially overlaps with one of the linear B-cell epitopes (ORF9b65-69). ORF3c CD4+T-cell epitopes (ORF3c2-16, ORF3c3-17 and ORF3c4-18) and linear B-cell epitope (ORF3c14-22) have also been identified as the candidate epitopes. Similarly, M.ext and 7a.iORF1 (overlap with M and ORF7a) proteins have promising immunogenic regions. By considering the level of antigen expression, 4 ORF9b and 5 M.ext epitopes are finally shortlisted as potent epitopes. Mutation analysis has further revealed that the shortlisted potent uORF epitopes are resistant to recurrent mutations. Additionally, 4 N-protein (expressed by canonical ORF) epitopes are found to be potent. Thus, SARS-CoV-2 uORF B-cell and T-cell epitopes identified here along with canonical ORF epitopes may aid in the design of promising polyvalent epitope vaccine (when connected through appropriate linkers) against SARS-CoV-2. Such a vaccine can act as a bulwark against SARS-CoV-2, especially in the scenario of emergence of variants with recurring mutations in the spike protein.